Endocrinology of the Testis and Male Reproduction - Simoni, Manuela; Huhtaniemi, Ilpo T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of endocrinology of the male reproductive system, explaining how it works and how, sometimes, it fails to work. World-class specialists present state of the art knowledge on all aspects, including anatomy, physiology, molecular biology, genetics, pathophysiology, clinical manifestations of testicular diseases, endocrine aspects of andrological and sexual diseases, and therapy. Extensive consideration is given to sexual development, testicular function, the clinical approach to disorders of male reproduction, male hypogonadism, sexual dysfunction, and male infertility. In addition, sociodemographic, psychological, and ethical aspects of male reproductive disorders are discussed. The book is intended as a major reference for endocrinologists, andrologists, and sexologists, as well as basic and clinical scientists. It is published as part of the SpringerReference program, which delivers access to living editions constantly updated through a dynamic peer-review publishing process.
GnRH Action -- Sex Determination -- Testicular Steroidogenesis and Testosterone -- Testis Development and Descent -- Anamnesis and Physical Examination -- The Semen Analysis -- Primary and Secondary Hypogonadism -- Gynecomastia -- Genetics of Male Infertility -- Varicocele -- Assisted Reporduction for Male Infertility -- Male Contraception -- Use, Misuse and Abuse of Androgens -- Ethical Aspects of Male Reproductive Disorders and Their Treatment.
Keywords: Medicine; Endocrinology; Reproductive medicine; Andrology; Medicine & Public Health; Endocrinology; Andrology; Reproductive medicine